Soybean superior progenies with resistance to type 3 soybean cyst nematode - Oliveira, RCC de; Di Mauro, A. O.; Uneda-Trevisoli, S. H.; Santos, J. M. dos; Oliveira, J. A. de; Perecin, D.; Arantes, N. E. (Empresa Brasil Pesq Agropec, 2005)
The aim of this work was to select in greenhouse soybean superior progenies resistant to type 3 soybean cyst nematode (Heterodera glycines). Ten agronomic traits were evaluated in 222 segregate progenies in field. In crop seasons of 1999/2000, 2000/2001 and 2001/2002, experiments were carried out in augmented blocks of Federer, and in 2002/2003 in a randomized blocks design, with two replications. In 2003 another experiment was carried out in greenhouse, under completely randomized design with five replications and with 11 superior progenies, in order to evaluate resistance against cyst nematode. Progenies JAB 99-17-4-9-1 and JAB 99-40-12-1-2 scored the best results for most of the agronomic traits evaluated. Under greenhouse conditions six progenies were resistant to type 3 soybean cyst nematode.
Keywords: Glycine max; Heterodera glycines; plant breeding